Unia Europejska – Ukraina: Czy wszystko zmieszało się na zawsze... - Krenz, Milena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Ukraine, which has been a sovereign state since 1991, is facing a dilemma whether it should direct its foreign policy towards Western Europe or intensify the collaboration within the framework of the Commonwealth of Independent States. Since the Ukraine has perceived itself as a geographical, cultural and historical part of Europe almost from the first days of independence she has undertaken to become permanently rooted in the family of European states. It was a consequence of the policy directed towardsWestern Europe and the United States that Kiev declared its readiness to become a rightful member of the European Union and NATO. Ukraine has combined her efforts to integrate with both these bodies, which is illustrated in the activity of Kiev that treats both these directions as the complementary elements of a single strategy and orientation towards the West.